Purification and properties of the manganese-dependent phosphoglycerate mutase of Bacillus subtilis. - Watabe, K (1979)
Phosphoglycerate mutase of Bacillus subtilis was purified to apparent homogeneity. It specifically required manganese ions for stability and activity, but it does not need 2,3-diphosphoglycerate as cofactor; the Km for Mn2+ is about 4.5 micrometer. Enzyme activity was inhibited by heavy-metal ions, 2,3-butanedione, and sulfhydryl agents. The mutase has a molecular weight of about 74,000 as shown by Sephadex gel filtration and by acrylamide gel electrophoresis in the presence of sodium dodecyl sulfate; it consisted of one polypeptide.